Differential expression of type I interferons in fetal tissues and the maternal-fetal interface in response to PRRSV infection - Sang, Wenjing (Kansas State University, 2012)
Interferons (IFNs) comprise a group of antiviral cytokines; however, their expression at the porcine maternal-fetal interface and in fetal tissues has not previously been investigated. The purpose of this study was to analyze the expression of type I IFNs and their receptors in maternal and fetal tissues from sows infected with PRRSV. The approach was to use real-time RT-PCR to identify the expression of different subtypes of type I IFN genes. The results show that the constitutive gene expression of some subtypes including IFN-[alpha] and IFN-[alpha][omega] were detected in fetal lymphoid nodes (IFN-[alpha][omega]), placenta (several IFN-[alpha] subtypes and IFN-[omega]5) and particularly, thymus (multiple IFN-[alpha], IFN-[delta] and IFN-[omega]5). The results demonstrate that porcine type I IFNs are differentially expressed at the maternal-fetal interface and in fetal tissues in response to PRRSV infection.
Keywords: PRRSV; Type I IFN expression; Biomedical Engineering (0541)